Approximate Algorithm for Fast Calculating Voltage Unbalance Factor of Three-Phase Power System - Wen, He; Cheng, Da; Teng, Zhaosheng; Guo, Siyu; Li, Fuhai (IEEE transactions on industrial informatics, 2014)
The method of calculating voltage unbalance factor (VUF) recommended by the IEC61000-4-27 has the disadvantage of requiring square root operation. This paper focuses on the fast and accurate calculation of VUF of three-phase power system. The approximate algorithm for calculating the magnitude of the zero, positive, and negative sequences by simple algebraic equation is presented. In the proposed method, the square root operation is first transformed to simple trigonometric equations based on the geometric figure, and then the trigonometric equations are approximated by the algebraic operations, which thus reduced the computation burden sufficiently. The simulation and practical experiment results show that the proposed method can achieve the same level of precision as the method recommended by the IEC61000-4-27, while much less clock cycles are required, which indicates its wide application in digital signal processor (DSP).